Perbandingan Efektivitas Mengunyah Buah Apel (Malus Sylvestris Mill) dan Buah Semangka (Citrullus Lanatus) Sebagai Self-cleansing Terhadap Perubahan Indeks Debris Pada Siswa Kelas VII SMPN 30 Kota Padang - Nadhila Hartari; Lendrawati Lendrawati; Bambang Ristiono (Andalas Dental Journal, 2021)
Debris is a leftover of food that found on the surface of an individual's teeth. Uncontrolled debris can cause dental caries. Eating fruits that contain fiber and water can reduce debris in the oral cavity, because it can increase salivary secretion during mastication. So that it can help the self-cleansing effect in the mouth. Objective: The purpose of this research was to find out the differences in the effectiveness of chewing apple (Malus sylvestris mill) with watermelon (Citrullus lanatus) as a self-cleansing in decreasing debris index in grade VII students of SMP 30 Kota Padang. Methods: This research used quasi-experimental design with pre and post-test design techniques that used purposive sampling with a 37 samples of people and consisted of two treatment groups. Self-administered questionnaire used to collect the information from respondent. Then, the data was analyzed by computerized analysts. Results: The average debris index before and after chewing apples has decreased by 1.170 with a standard deviation of 0.302. Then, the average debris index before and after chewing the watermelon decreased by 0.612 with a standard deviation of 0.17, according to the Wilcoxon test showed the p value of is 0,000 (p <0.05). Conclusion: There are significant differences from the results of the debris index before and after consuming apples and watermelons in the two treatment groups. In the Mann Whitney test showed a value of p = 0,000 (p <0.05)